Proteomics research in forest trees: A 2012-2022 update - Castillejo, María Angeles; Pascual, Jesús; Jorrín-Novo, Jesus V.; Balbuena, Tiago Santana (Frontiers in Plant Science, 2023)
This review is a compilation of proteomic studies on forest tree species published in the last decade (2012-2022). It is mostly focused on the most investigated species, including Eucalyptus, Pinus, and Quercus. Continuous improvements and novelties of different analytical platforms, coupled with increasing availability of genomic data and resources for these species have contributed to great advances in the knowledge of their biology at the molecular, organismal, and community levels. Integration of proteomics with physiological, biochemical, and other large-scale studies has been mostly used for a comprehensive understanding of different biological processes and their translation to the productive sectors. We envisage that proteomics in long-living plants will thrive in light of the most recent global climate change discussions, acting as key players in both climate mitigation strategies and molecular breeding programs.